Management decision based on lymphovascular involvement leads to favorable outcomes after endoscopic treatment of esophageal squamous cell carcinoma - Takahashi, Kazuya; Hashimoto, Satoru; Mizuno, Ken-ichi; Kobayashi, Takamasa; Tominaga, Kentaro; Sato, Hiroki; Kohisa, Junji; Ikarashi, Satoshi; Hayashi, Kazunao; Takeuchi, Manabu; Yokoyama, Junji; Kawai, Hirokazu; Sato, Yuichi; Kobayashi, Masaaki; Terai, Shuji (Endoscopy, 2018)
Background Esophageal squamous cell carcinoma (ESCC) invading the muscularis mucosae (MM) and submucosa up to 200 µm (SM1) has a risk of metastasis. The aims of this study were to investigate the long-term outcome of endoscopic submucosal dissection (ESD) for MM/SM1 ESCC and to assess the management after ESD in our hospital.Methods This was a retrospective cohort study conducted at a single institution. Patients with MM or SM1 ESCC who were treated with ESD were included. Additional prophylactic therapy was added if lymphovascular involvement (LVI) was noted in the ESD specimens. Results A total of 102 patients were analyzed. The median length of follow-up was 71.5 months (range 9 – 144 months) and the median number of CTs was 6 (range 0 – 24). LVI was found in 21 patients (20.6 %), and 12 patients underwent additional prophylactic therapy. The 5-year overall survival, disease-specific survival, and tumor-free survival rates were 84.1 %, 97.5 %, and 82.1 %, respectively. A total of 26 patients died, but only 2 of them died from ESCC. The cumulative metastasis rate was 11.8 %, and LVI was a significant predictor of metastasis (hazard ratio 5.42, 95 % confidence interval 1.39 – 21.18; P = 0.02). There were no differences between patients with MM ESCC and those with SM1 ESCC. Conclusions The long-term outcome after ESD for MM/SM1 ESCC was favorable with additional prophylactic therapy and strict adherence to follow-up. These results indicate that our management decision based on LVI is a valid approach and that ESD can be offered as a therapeutic option to MM/SM1 ESCCs.